Atomic scale structure of sputtered metal multilayers - Zhou, X.W.; Wadley, H.N.G.; Johnson, R.A.; Larson, D.J.; Tabat, N.; Cerezo, A.; Petford-Long, A.K.; Smith, G.D.W.; Clifton, P.H.; Martens, R.L.; Kelly, T.F. (Acta materialia, 2001)
A combined theoretical and experimental approach has been used to study nanoscale CoFe/Cu/CoFe multilayer films grown by sputter deposition. Such films have applications in sensors that utilize the giant magnetoresistance effect, for example, read heads in high-density information storage devices. Atomistic simulations based on a molecular dynamics approach and an alloy form of the embedded atom method have been developed to accurately model the sputter deposition of the CoFe/Cu/CoFe multilayers. The simulations show that relatively flat interfaces are formed because of the energetic deposition conditions. However, significant intermixing at the CoFe-on-Cu interface, but not at the Cu-on-CoFe interface, was observed. An abnormal Fe depletion zone is also revealed at the CoFe-on-Cu interface. A three-dimensional atom probe method has been used for a nanoscale chemical analysis of the films. It provided direct verification of the simulations. The simulations have then been used to understand the mechanism responsible for the formation of the intermixing defects observed in the multilayers. A novel deposition technique is proposed which reduces both interfacial mixing and Fe depletion by controlling the incident adatom energies.